Clinical and Neuroimaging Features in a Patient with Non-Ketotic Hyperglycemia - Yonghua Zhang; Aasheeta Parikh (MDPI AG, 2020)
Hemichorea-hemiballism (HC-HB) is a spectrum of involuntary flinging and flailing, non-patterned, irregular movements involving one side of the body. A rare dysfunction of glucose metabolism leading to a state of non-ketotic hyperglycemia (NKH) is thought to be a cause of these symptoms. In previous case studies, imaging findings have been in the basal ganglia as hyperintense lesions on magnetic resonance imaging (MRI) or hyperdensities on computerized tomography (CT). This case is unique due to abnormal findings in the MRI T2/fluid-attenuated inversion recovery (FLAIR) sequence in areas not previously reported-the thalamus and midbrain/pons. As in other NKH cases, the patient improved both clinically and radiologically. In patients with uncontrolled diabetes and abnormal movements, monitoring of blood glucose is imperative as it can lead to recognition of HC-HB. Other etiologies, including stroke, neoplasm, demyelination, and inflammatory processes, have uncertain prognoses with unfavorable outcomes. The prognosis for NKH is usually favorable, and thus important to identify.